PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA LUBUKLINGGAU - Suwarno Suwarno; Thoto Massat (Jurnal Media Ekonomi (JURMEK), 2017)
The study entitled Effect of leadership and organizational culture on the performance of employees in the industrial and trade offices of Lubuklinggau City. This study aims to determine the effect of leadership and organizational culture on employee performance. The sample in this study is 65 employees. Data was collected through questionnaires answered by respondents and then analyzed by multiple regression analysis techniques, using a computer program "Statistical Product For Service Solaction" (SPSS) for Windows Release 17.00. From the calculation of the coefficient of determination, it can be seen that the R2 value is 0.365, this indicates that the leadership variables and organizational culture together provide controversy on employee performance variables of 60.4% and after adjusting the remaining value of 39.6% is influenced by other variables not included in this study. The results of the analysis show that: the results of the regression analysis obtain a regression equation: Y = 8.149 + 0.463X1 + 0.349X2. From the estimation equation of the regression function above, it can be seen that the value of the constant (a) obtained is 8.149, the value b1 = 0.463, b2 = 0.349, and the value a = 8.149. This illustrates that without being influenced by the independent variable (X), the performance of the employees of the Lubuklinggau City Office of Industry and Trade is 8,149. Regression coefficient values ​​represent leadership variables obtained at 0.463 indicating that each change in leadership teacher performance will change proportionally, that is equal to 0.463 assuming other independent variables are constant. The value of the regression coefficient represents the organizational culture variable obtained at 0.349 indicating that each change in organizational culture, the employee's performance will change directly, which is equal to 0.349 assuming the other independent variables are constant. Based on the results of the analysis obtained, the value of Ftable is 2.75, while Fcount is 17,825 with sig 0,000 if Fcount = 17,825> Ftable 2.75, Ha is accepted. So that it can be concluded that leadership and organizational culture have a significant effect on the performance of the employees of the Department of Industry and Trade of Lubuklinggau City.